If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -2x) = -9 (4 * 3 + -2x * 3) = -9 (12 + -6x) = -9 Solving 12 + -6x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6x = -9 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = -9 + -12 -6x = -9 + -12 Combine like terms: -9 + -12 = -21 -6x = -21 Divide each side by '-6'. x = 3.5 Simplifying x = 3.5
| Cos(3.1416/6) | | W(20)=13.2x+443 | | 4r-7+6r=19 | | 17=8t-36 | | Y=2x^2+12x-91 | | 7y=5-12 | | 3x^2+16-5=0 | | x/4-1/6≤12 | | -12=.2/f | | 277+96+277x+277y=376 | | 4xy-5x+4y^3=-40 | | 4(5x-4(5x+y))= | | Y=2.3x+0.2 | | 171=3x+2x^2 | | -21-18y+y=13 | | e^4x+2e^2x-24=0 | | 1000*q=1.4597 | | log81^1/9=x | | 3*-7-6y+y=13 | | 12p-15+6p=-27 | | 18x=x+y | | 0=-2x^2-10x | | Y=-0.3x-5.3 | | 2x^2+2x+25=289 | | 3ab-ab+b= | | 96+.18x+.20x=376 | | 6/x^2 | | 3(-7-6y)-y=13 | | 6x+10=35-9x | | 18-x+x+14-x+5=36 | | 2x^2-31x-475=0 | | 5/6x-4/5=0 |